Draft genome and SSR data mining of a Peruvian landrace of Capsicum chinense, the arnaucho chili pepper - Estrada, Richard (2024)
The Arnaucho chili pepper (ACP) is a traditional vegetable used in Peru because of its gastronomic properties. Due to its importance in the Peruvian diet and economy, this species is a resource that can be a candidate to plant breeding programs. In this study, the complete genome nucleotide sequence of this chili pepper was generated using the Illumina Hiseq 2500 sequencing technology. We sequenced the whole genome of the ACP using a paired-end 150 strategy, obtaining 330.46 GB of sequencing data. The genome size of the ACP was 2.98 Gb with a contig N50 of 237 Mb and 95.39% complete BUSCOs. Also, we identified 71.96% of repetitive DNA of the genome assembly, of which retroelements occupy 37.95% of the total genome. We downloaded genomes of the Solanoideae subfamily and conducted a comparative analysis of simple sequence repeats (SSRs) with our draft genome, and we identified lower number of SSRs in the ACP genome compared to other pepper species. This first ACP genome is expected to contribute to a better understanding of its genetics to adapt to the arid conditions of the Peruvian coastal ecosystem and evolution.